Impelementasi Metode MOORA Pada Sistem Pendukung Keputusan Pemilihan Pegawai Teladan - Amat Damuri; Tuti Lisnawati; Wieke Tsanya Fariati; Rhaishudin Jafar Rumandan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Employees are a human resource asset for a company in carrying out the operational activities of an organization or company in achieving the main goals of the organization or company. The purpose of this study is to select exemplary employees in the company using the MOORA method, so that the company will quickly evaluate exemplary employees once every 6 months. The results of the ranking of exemplary employees who get rank 1 are exemplary employees, namely Zaenal Yuswantoro with a total score of 0.179431073, for rank 2 exemplary employees, namely Yolanda Prasasti with a total score of 0.175703146, and 3rd rank exemplary employees, namely Ahmad Budianto with a total value of 0.174341166. The results of manual calculations and by using a web application based on the Laravel framework show no difference in the results of the grades and ratings of the employees being assessed